Efficacy of commercial molluscicide formulations against the golden apple snail Pomacea canaliculata - De La Cruz, M. S.; Joshi, R. C. (2001)
Four commercial molluscicide formulations were re-evaluated for their efficacy on the golden apple snail (GAS), Pomacea canaliculata (Lamarck), during the dry and wet seasons of 2000: niclosamid 250 EC, metaldehyde 75WP, metaldehyde 300 Fl, and metaldehyde 6% pellets. Field experiments in Muñoz, Nueva Ecija in the Philippines using microplot technique revealed that all commercial molluscicide formulations were effective against GAS, resulting in up to 69% mortality during the dry season and 90% during the wet. Efficacy lasted up to 3 days, after which there was zero mortality, except with metaldehyde 6% pellets which gave 4% mortality during the dry season.
Keywords: Snails; Golden apple snail; Pesticides